Effectiveness of clinician client centered counseling on condom use and status disclosure of adult HIV positive patients enrolled in care in Yola, Nigeria: a randomized clinical trial - Martins, Olutayo Folashade; Gyanchand Rampal, Lekhraj Rampal; Lye, Munn Sann; Mohd Sidik, Sherina; Othman, Norlijah; Iliyasu, Zubairu; Salawu, Fatai Kunle (The International Journal of Health Sciences and Research, 2016)
This study assessed the effectiveness of a developed and implemented Clinician Client Centered Counseling Module on improving condom use and increasing HIV status disclosure to spouses and or sex partners of adult patients living with HIV enrolled in care in Yola, Nigeria. The study was a three arm randomized single blind clinical trial involving 386 randomly selected and allocated adult patients living with HIV who were enrolled into ART care at any of the four comprehensive ART sites in Yola. A clinician client centered training module was developed based on the Information Behavior and Motivation (IBM) Model. Nine Clinicians involved in ART care were trained with this module to deliver a 10 to 15 minutes clinic based intervention (Clinician Client Centered counseling). Intervention group one received two counseling sessions; at baseline and at two month, intervention group two received a counseling session at baseline and the control group received routine care. An interviewer administered structured questionnaire was used for data collection. Data was collected at baseline, two months and six months. Outcome measures were condom use and HIV status disclosure. Data was analyzed using SPSS version 22. At six months a significantly higher median condom use score was seen in intervention group one compared to intervention group two (1.00 vs 0.50; p = 0.01), and in intervention group one compared to the control group (1.00 vs 0.00; p = 0.01). A significant change in median condom use scores from baseline to 6 months was seen for intervention group one (p = 0.02). At six months a significantly higher mean HIV status disclosure was seen in intervention group one compared to the control group (0.30 vs 0.25; p = 0.01) and in the intervention group two compared to the control group (0.30 vs 0.25; p = 0.01). A significant main effect for time was seen for HIV status disclosure to spouse and/or sexual partners (p = 0.01). Clinician Client Centered counseling is an effective behavioral intervention in improving condom use and status disclosure of adult patients living with HIV.